Environmental impact assesments and territory : Contributions from the perspective of territorial understanding, intelligence and development - Bozzano, Horacio (Territorial intelligence and culture of development)
Is it possible to incorporate territorial understanding, intelligence and development (TUID) in environmental and urban impact assessments (EIAs)? In this paper we intend to provide some answers to this compelling question. We present some theoretic-methodological criteria that emerged after jointly1 working on approximately forty EIAs, mainly on urban environments in Argentina.